1975
DOI: 10.1111/j.1476-5381.1975.tb07349.x
|View full text |Cite
|
Sign up to set email alerts
|

Tryptamines and Some Other Substances Affecting Waking and Sleep in Fowls

Abstract: IAdult fowls (Gallus domesticus) with cannulae chronically implanted in the IlIrd cerebral ventricle and various other sites of the brain, received infusions or injections of tryptamines and catecholamines into the brain; effects of and interactions between these substances on behaviour, electrocortical activity and body temperature were studied. Reserpine-induced arousal, was investigated in young and adult fowls.2 Tryptamine and ci-methyltryptamine, given intraventricularly or into the hypothalamus of intact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1977
1977
1993
1993

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Such embryos did not produce CEF capable of synthesizing the 25K polypeptide, nor did they contain functional mRNA coding for it, as judged by in vitro translation. DISCUSSION Our experiments showed that major changes in gene expression occur in the cells of most organs of a living endothermic organism as its body temperature is increased from its normal value to those extreme values which can just be tolerated by the organism, at least for a limited time span (1,16,21). A few characteristic proteins, the HSPs which are synthesized at low rates at normal temperatures, became the predominant protein products at such elevated temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Such embryos did not produce CEF capable of synthesizing the 25K polypeptide, nor did they contain functional mRNA coding for it, as judged by in vitro translation. DISCUSSION Our experiments showed that major changes in gene expression occur in the cells of most organs of a living endothermic organism as its body temperature is increased from its normal value to those extreme values which can just be tolerated by the organism, at least for a limited time span (1,16,21). A few characteristic proteins, the HSPs which are synthesized at low rates at normal temperatures, became the predominant protein products at such elevated temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Our experiments showed that major changes in gene expression occur in the cells of most organs of a living endothermic organism as its body temperature is increased from its normal value to those extreme values which can just be tolerated by the organism, at least for a limited time span (1,16,21). A few characteristic proteins, the HSPs which are synthesized at low rates at normal temperatures, became the predominant protein products at such elevated temperatures.…”
Section: Discussionmentioning
confidence: 76%
“…However, distinct receptors for tryptamine and 5HT may exist as suggested by opposing pharmacological actions (Cox & Lee, 1980;Marley & Nistico, 1975) and by differential inhibition of comparable tryptamine and 5HT-induced behavious (Clineschmidt & Lotti, 1974). We now report the characteristics of tryptamine-induced (plus a monoamine oxidase inhibitor) myoclonus in guinea-pigs in comparison to the 5HTP-induced behaviour.…”
Section: When 15t [85sr]-labelled Microspheres Werementioning
confidence: 99%